The formation of reference points in consumer choice behavior: Experimental evidence from a fish market in Nigeria - Shikuku, Kelvin Mashisia; Bulte, Erwin; Lagerkvist, Carl Johan; Tran, Nhuong (International Association of Agricultural Economists, 2021)
We study the role of endowments and expectations in the construction of reference points in the context of fish trading on fish markets in Nigeria. In our field experiment, consumers can trade a known food item for a novel, superior food item (and vice versa). Endowments matter for reference point formation, but the effect of expectations about future ownership is mixed. While expectations affect bidding behavior for subjects “trading up”, it does not affect bids for subjects “trading down”. We probe the role of aspirations as a mediating factor but document no evidence in support of it.